Ultra-processed food consumption and associations with biomarkers of nutrition and inflammation in pregnancy: The Norwegian Environmental Biobank - Kelsey, Pieta Tasnim; Papadopoulou, Eleni; Borge, Tiril Cecilie; Dahl, Cecilie; Brantsæter, Anne Lise; Erlund, Iris; Meltzer, Helle Margrete; Haug, Line Småstuen; Caspersen, Ida Henriette (Frontiers in Nutrition, 2022)
Background A high consumption of ultra-processed foods (UPFs) is often associated with low nutritional quality, but data on associations with biomarkers are scarce. We aimed to explore associations between UPF intake, diet quality, and concentrations of biomarkers of nutrition and inflammation measured in mid-pregnancy. Methods This cross-sectional study included n = 2,984 pregnant women recruited during 2002–2008 in the Norwegian Mother, Father, and Child Cohort Study (MoBa). Concentrations of C-reactive protein (CRP) and 21 nutritional biomarkers including carotenes (α-carotene, β-carotene, γ-carotene, α-cryptoxanthin, β-cryptoxanthin, lutein, lycopene), vitamins [α-tocopherol, γ-tocopherol, 25-hydroxyvitamin D (25-OH-D), retinol], creatinine, elements (K, Na, Co, Cu, Mn, Mo, Se, Zn), and ferritin (Fe) were measured in blood and urine collected in mid-pregnancy. Habitual diet in pregnancy was assessed using a validated semi-quantitative food frequency questionnaire. We calculated the relative (%) energy contribution of UPF to overall intake according to the NOVA classification. We also applied a diet quality index (DQI) adapted to assess adherence to Norwegian dietary guidelines (DQI; min–max: 0–110, higher score meaning higher adherence). We present summary statistics for biomarker concentrations and explored associations between UPF intake or the DQI and measured biomarkers using adjusted linear, logistic, and generalized additive regression models. Results Ultra-processed food intake was positively associated with biomarker concentrations of vitamin E (γ-tocopherol), creatinine, K, and Na [βs: 5.6 to 17% increase in biomarker concentration per interquartile range (IQR) increase in UPF intake] and negatively associated with carotenoids (α-carotene, β-carotene, γ-carotene, α-cryptoxanthin, β-cryptoxanthin, lutein, lycopene), vitamin A, Mo, and Se (βs: −2.1 to −18%). Inversely, high diet quality (i.e., the DQI) was positively associated with concentrations of carotenoids, vitamins [vitamin A (retinol) and D (25-OH-D)], and Se (β: 1.5 to 25%) and negatively associated with vitamin E (γ-tocopherol), creatinine, and Na (β: −4.8 to −8.3%). A weak, positive association was found between UPF and CRP (β: 5.4%, 95% CI 0.12–11%). Conclusion High UPF intake was associated with reduced concentrations of nutrition biomarkers in mid-pregnancy. Associations in the opposite direction were found with high adherence to the Norwegian dietary guidelines, suggesting that the two dietary scoring systems capture diet quality in a mirrored manner in this population.